2013
DOI: 10.1111/j.1399-0004.2012.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mosaicism in a mother of two children with Pitt–Hopkins syndrome

Abstract: Pitt-Hopkins syndrome (PTHS) is a neurodevelopmental disorder characterized by intellectual disability, unusual face and breathing abnormalities and can be caused by haploinsufficiency of TCF4. The majority of cases are sporadic. Somatic mosaicism was reported infrequently. We report on a proband with typical manifestations of PTHS and his younger brother with a less striking phenotype. In both, a heterozygous frameshift mutation (c.1901_1909delinsA, p.Ala634AspfsX67) was found in exon 19 of TCF4. The same mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…Recurrence risk for sibs of affected individuals is therefore generally low. Germ line or low‐grade parental mosaicism has been reported in four instances, representing 2% to 3% of published cases . Additionally, our joint experience in 273 individuals with molecularly confirmed PTHS indicates five recurrences in siblings without a detectable (mosaic) TCF4 variant in the parents.…”
Section: Molecular Diagnostic Criteriamentioning
confidence: 72%
See 1 more Smart Citation
“…Recurrence risk for sibs of affected individuals is therefore generally low. Germ line or low‐grade parental mosaicism has been reported in four instances, representing 2% to 3% of published cases . Additionally, our joint experience in 273 individuals with molecularly confirmed PTHS indicates five recurrences in siblings without a detectable (mosaic) TCF4 variant in the parents.…”
Section: Molecular Diagnostic Criteriamentioning
confidence: 72%
“…Germ line or low-grade parental mosaicism has been reported in four instances, representing 2% to 3% of published cases. 15,22,42,43 Additionally, our joint experience in 273 individuals with molecularly confirmed PTHS indicates five recurrences in siblings without a detectable (mosaic) TCF4 variant in the parents. Therefore, we confirm an empiric recurrence risk of up to 2% (R4).…”
Section: Pattern Of Inheritancementioning
confidence: 90%
“…Although the majority of cases of PTHS arise as a result of sporadic, spontaneous mutations in the TCF4 gene, Steinbusch et al 43 have reported somatic mosaicism of the TCF4 gene in a mother with two children manifesting PTHS. In both children, a heterozygous frameshift mutation (c.1901_1909delinsA, p.Ala634AspfsX67) was found in exon 19 of TCF4: the same mutation was found at low levels in DNA from the mother.…”
Section: Differential Diagnosis—discovery Of the Tcf4 Transcription Fmentioning
confidence: 99%
“…In both children, a heterozygous frameshift mutation (c.1901_1909delinsA, p.Ala634AspfsX67) was found in exon 19 of TCF4: the same mutation was found at low levels in DNA from the mother. As Steinbusch et al 43 suggest, the possibility of familial recurrence with somatic mosaicism in a healthy mother has important consequences for genetic counseling of PTHS families. This consideration may also explain an early report of possible PTHS in two siblings, 28 although an alternative explanation could be the more recently characterized possibility of manifestation of a PTHS-like ID disorder manifesting autosomal recessive inheritance through NRXN1 and CNTNAP2 mutations, as will be described in the next paragraph.…”
Section: Differential Diagnosis—discovery Of the Tcf4 Transcription Fmentioning
confidence: 99%
“…De novo mutations, germline mosaicism and other complexities Although this concept of somatic mosaicism has been in the literature for many years [131][132][133][134][135], it is really only recently that more people are beginning to realize that it might be much more extensive in humans than previously thought [23,[136][137][138][139][140][141][142][143][144][145][146][147][148][149]. In fact, hardly anything is truly known regarding the extent of somatic mosaicism in humans and its effect on phenotype in even well studied diseases.…”
Section: "Those Who Have Given Any Attention To Congenital Mental Lesmentioning
confidence: 99%